Combined V-Y Fasciocutaneous Advancement and Gluteus Maximus Muscle Rotational Flaps for Treating Sacral Sores. (6th June 2016) - Han, Hyun Ho; Choi, Eun Jeong; Moon, Suk Ho; Lee, Yoon Jae; Oh, Deuk Young
Abstract : The sacral area is the most common site of pressure sore in bed-ridden patients. Though many treatment methods have been proposed, a musculocutaneous flap using the gluteus muscles or a fasciocutaneous flap is the most popular surgical option. Here, we propose a new method that combines the benefits of these 2 methods: combined V-Y fasciocutaneous advancement and gluteus maximus muscle rotational flaps. A retrospective review was performed for 13 patients who underwent this new procedure from March 2011 to December 2013. Patients' age, sex, accompanying diseases, follow-up duration, surgical details, complications, and recurrence were documented. Computed tomography was performed postoperatively at 2 to 4 weeks and again at 4 to 6 months to identify the thickness and volume of the rotational muscle portion. After surgery, all patients healed within 1 month; 3 patients experienced minor complications. The average follow-up period was 13.6 months, during which time 1 patient had a recurrence (recurrence rate, 7.7%). Average thickness of the rotated muscle was 9.43 mm at 2 to 4 weeks postoperatively and 9.22 mm at 4 to 6 months postoperatively (p = 0.087 ). Muscle thickness had not decreased, and muscle volume was relatively maintained. This modified method is relatively simple and easy for reconstructing sacral sores, provides sufficient padding, and has little muscle donor-site morbidity.